Pulmonary Vein Occlusion Requiring Lobectomy after Radiofrequency Catheter Ablation for Atrial Fibrillation: A Case Report and Review of the Literature - Jagelavičius, Žymantas; Baužienė, Ana; Jovaišas, Vytautas; Janilionis, Ričardas (Lietuvos chirurgija, 2023)
Pulmonary vein stenosis is a potential complication after radiofrequency ablation for atrial fibrillation. We present an unusual case of this complication that progressed to vein occlusion and required lobectomy and review the literature. A 54-year-old man presented with persistent chest pain, dry cough, and hemoptysis. Seven months before he underwent radiofrequency catheter ablation for atrial fibrillation. Chest computed tomography showed a narrowing of the left lower pulmonary vein after the procedure. The patient was treated conservatively. On the presentation, a chest computed tomography scan showed total pulmonary vein occlusion. A quantitative ventilation/perfusion scan revealed no perfusion to the left lower lobe. A balloon angioplasty was performed, however unsuccessfully. The left lower lobectomy was performed. Six years after the lobectomy the patient has neither cardiac nor pulmonary symptoms. Pulmonary vein occlusion after radiofrequency ablation for atrial fibrillation leading to lung resection is still a possible severe complication.